A Comparative Study on Two Types of Porcine Acellular Dermal Matrix Sponges Prepared by Thermal Crosslinking and Thermal-Glutaraldehyde Crosslinking Matrix Microparticles - Huang, Xing; Ding, Yi; Pan, Wenqian; Lu, Lin; Jin, Rui; Liang, Xiao; Chang, Mengling; Wang, Yinmin; Luo, Xusong (Frontiers in Bioengineering and Biotechnology, 2022)
Common commercial porcine acellular dermal matrix (PADM) products take the form of a thin membrane. Given its dense structure, delaying vascularization after implantation remains an issue to be solved. In addition, overlaying multiple sheets to address deep wounds and large tissue defects that are difficult to repair by self-tissues could hinder tissue ingrowth, angiogenesis, and integration. Here, we creatively prepared PADM microparticles through a homogenizing treatment and crosslinked them to ADM sponges using thermal crosslinking (VT-ADM) and thermal-glutaraldehyde crosslinking (GA-ADM). The resulting VT-ADM was thicker than GA-ADM, and both maintained natural dermal matrix microstructure and thermal stability. The porosity of GA-ADM (mean 82%) was lower than that of VT-ADM (mean 90.2%), but the mechanical strength and hydrophilicity were significantly higher. The two types of ADM-sponges showed no obvious difference in cell adhesion and proliferation without cytotoxicity. Furthermore, the human adipose stem cells were co-cultured with ADM sponges which promoted proliferation, tube formation and migration of endothelial cells, and the GA-ADM group exhibited better migration behavior. There were no markable differences among expressions of pro-angiogenesis genes, including vascular endothelial growth factor, insulin-like growth factor-1 and epidermal growth factor. In a nude mice model, the VT-ADM and GA-ADM pre-cultured with human adipose stem cells for 1 week in advance were implanted subcutaneously. The VT-ADM and the GA-ADM showed great histocompatibility without local redness, swelling or necrosis. The vascular density of the local skin flap above the material was visualized using Indocyanine green and showed no statistical difference between the two groups. The collagen tissue deposition in the pores and vessel formation within the sponges increased with time. Although VT-ADM had a higher degradation rate in vivo, the integrity of the two scaffolds was preserved. Collectively, the VT-ADM and the GA-ADM retained natural matrix structure and presented biocompatibility. Thus, the above-mentioned two crosslinking methods for ADM sponges are safe and practicable. The novel ADM sponges with good physicochemical and biological properties are no longer limited to membrane tissue regeneration but could also realize structure remodeling where they act as scaffolds for soft tissue filler and three-dimensional reconstruction of the tissue with strength requirements.